Synergic effects of thermal mass and natural ventilation on the thermal behaviour of traditional massive buildings. Issue 5 (27th May 2016) - Gagliano, A.; Nocera, F.; Patania, F.; Moschella, A.; Detommaso, M.; Evola, G.
Abstract : The energy policies about energy efficiency in buildings currently focus on new buildings and on existing buildings in case of energy retrofit. However, historic and heritage buildings, that are the trademark of numerous European cities, should also deserve attention; nevertheless, their energy efficiency is nowadays not deeply investigated. In this context, this study evaluates the thermal performance of a traditional massive building situated in a Mediterranean city. Dynamic numerical simulations were carried out on a yearly basis through the software DesignBuilder, both in free-running conditions and in the presence of an air-conditioning (AC) system. The results highlight that the massive envelope of traditional residential buildings helps in maintaining small fluctuations of the indoor temperature, thus limiting the need for AC in the mid-season and in summer. This feature is highly emphasised by exploiting natural ventilation at night, which allows reducing the building energy demand for cooling by about 30%.The research also indicates that, for Mediterranean climate, the increase in thermal insulation does not always induce positive effects on the thermal performance in summer, and that it might even produce an increase in the heat loads due to the transmission through the envelope.